2021
DOI: 10.1111/jir.12814
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a syndrome‐informed micro‐intervention for infants with Down syndrome

Abstract: Background Infants with Down syndrome (DS) are at risk for a range of phenotypic outcomes, including delays in the onset of reaching behaviour, a critical skill that facilitates early learning. This parallel‐group feasibility and pilot study presents findings from a parent‐mediated micro‐intervention that aimed to support the development of reaching behaviour in a sample of infants with DS. Methods Participants were 73 infants with DS and their caregivers. Infants who qualified for the home‐based intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Rarely, there are effective treatments available such as the ketogenic diet for glucose transporter 1 deficiency syndrome (Klepper et al, 2020). While none of the supportive treatments available are curative for most NDDs, early intervention has been demonstrated to improve outcomes for Down Syndrome and other NDDs (Fidler et al, 2021;Guralnick, 2010Guralnick, , 2011Pinero-Pinto et al, 2020;Wojcik et al, 2020). Furthermore, in the conceptual framework established with SMA, the concurrent pilot NBS study and clinical trial with nusinersen were structured to co-evolve, enabling early identification of newborns during a critical therapeutic window in which treatments were most efficacious.…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, there are effective treatments available such as the ketogenic diet for glucose transporter 1 deficiency syndrome (Klepper et al, 2020). While none of the supportive treatments available are curative for most NDDs, early intervention has been demonstrated to improve outcomes for Down Syndrome and other NDDs (Fidler et al, 2021;Guralnick, 2010Guralnick, , 2011Pinero-Pinto et al, 2020;Wojcik et al, 2020). Furthermore, in the conceptual framework established with SMA, the concurrent pilot NBS study and clinical trial with nusinersen were structured to co-evolve, enabling early identification of newborns during a critical therapeutic window in which treatments were most efficacious.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the complexity of these potential associations and how they may unfold over time, it is important to identify and characterise sources of developmental profile variability in young children with DS. Shedding light on these issues is of interest in research and in clinical settings, as it can promote tailored, early interventions and guidance (Fidler et al ., 2021). Planning more specific interventions may positively influence developmental trajectories, thereby improving the quality of life for individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…Infant action planning was measured with a reaching task (Barrett et al 2008). A similar version of this measure is described in Fidler et al (2021), which reported findings on a subset of infants with DS included in the current study. Two balls, each with different properties (varying soft textures), were placed in front of the infant at midline, one at a time.…”
Section: Executive Function Precursorsmentioning
confidence: 99%